2017
DOI: 10.1111/resp.13046
|View full text |Cite
|
Sign up to set email alerts
|

Randomized cross‐over trial of ventilator modes during non‐invasive ventilation titration in amyotrophic lateral sclerosis

Abstract: ST mode shows better results in gas exchange, respiratory events and PVA. Nevertheless, accurate NIV titration remains necessary as some patients show equal or better results when using the S mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 35 publications
0
10
0
12
Order By: Relevance
“…29 Vrijsen et al found that residual nocturnal respiratory events under NIV were prevalent in patients with amyotrophic lateral sclerosis, justifying screening with polysomnography under NIV. 30 However, a single night in a sleep laboratory may be insufficient to fully correct nocturnal events. Moreover, access to in-lab may be limited by bed availability and cost.…”
Section: Connectivity Via External Plugin §mentioning
confidence: 99%
“…29 Vrijsen et al found that residual nocturnal respiratory events under NIV were prevalent in patients with amyotrophic lateral sclerosis, justifying screening with polysomnography under NIV. 30 However, a single night in a sleep laboratory may be insufficient to fully correct nocturnal events. Moreover, access to in-lab may be limited by bed availability and cost.…”
Section: Connectivity Via External Plugin §mentioning
confidence: 99%
“…Low‐level inspiratory pressure support is generally sufficient when initiating NIV. Semi‐controlled pressure modes (spontaneous modes with back‐up frequency) are preferred, being more effective in ALS than spontaneous modes . Ventilator settings can then be adjusted to ensure sufficient inspiratory assistance to obtain normal daytime and nocturnal PaCO 2 .…”
Section: How Should Als Patients Be Ventilated?mentioning
confidence: 99%
“…Pressure assist‐control ventilation does not need to be changed to volume assist‐control ventilation in ventilator‐dependent patients. A semi‐controlled mode with back‐up rate is sufficient, even in 24‐h‐a‐day ventilator‐dependent patients. The security of ventilation, the presence of alarms and batteries, the dimensions, simplicity (or complexity) and noise are not better, at the present time, with either pressure assist‐control or volume assist‐control ventilators.…”
Section: How Should Als Patients Be Ventilated?mentioning
confidence: 99%
“…While venous bicarbonate sampling may be used to screen for sleep hypoventilation particularly for obesity hypoventilation syndrome, raised levels may also reflect multimorbidity in this population . As shown by O’Donoghue et al, the development of awake hypercapnia and sleepiness in patients with myotonic dystrophy is not necessarily a consequence simply of sleep‐disordered breathing, raising issues of disease‐specific guidelines for NIV timing, modes of ventilation and expected outcomes . Mask fitting is critical in minimizing complications and improving NIV efficacy.…”
Section: Sleepmentioning
confidence: 99%